2012
DOI: 10.1037/a0025959
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol-A impairs memory and reduces dendritic spine density in adult male rats.

Abstract: Exposure to Bisphenol-A (BPA), an endocrine disruptor used in plastics, occurs in the United States on a daily basis. Recent studies suggest exposure during development causes memory deficits later in life, however the ramifications of exposure in adulthood are unclear. We examined the effects of acute BPA administration (40μg/kg) on memory and synaptic plasticity in adult male rats. BPA significantly impaired both visual and spatial memory and decreased dendritic spine density on pyramidal cells in CA1 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
95
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 85 publications
10
95
0
1
Order By: Relevance
“…[[qv: 5b]] In addition, prenatal BPA exposure results in reduced spine number on the hippocampal CA1 areas of neonates African green monkeys and adult mice (14 month old). [[qv: 9a,27]] Even one injection of BPA (40 µg kg −1 ) can reduce dendritic spine density in the CA1 areas of adult male rats 22. Although exposure time, BPA dosage and experimental subjects of our study are different with those previous studies, the results are consistent with their morphological alterations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[[qv: 5b]] In addition, prenatal BPA exposure results in reduced spine number on the hippocampal CA1 areas of neonates African green monkeys and adult mice (14 month old). [[qv: 9a,27]] Even one injection of BPA (40 µg kg −1 ) can reduce dendritic spine density in the CA1 areas of adult male rats 22. Although exposure time, BPA dosage and experimental subjects of our study are different with those previous studies, the results are consistent with their morphological alterations.…”
Section: Discussionsupporting
confidence: 79%
“…According to previous reports, one week BPA exposure (40 µg kg −1 d −1 ) in adolescent rats impairs the object placement performance, which is also hippocampal‐dependent spatial memory 8. Moreover, acute BPA exposure in adult rats could cause the impairment of object placement memory 22. Our findings provide important “missing” evidence of BPA effects on hippocampal‐related function in the whole life of rats.…”
Section: Discussionsupporting
confidence: 74%
“…PSD -95 is located in dendritic spines and is a key post-synaptic scaffold protein at excitatory synapses that directly promotes synapse maturation and exerts a major influence on synaptic strength and plasticity (40). Previous studies have shown that an increase in PSD -95 is correlated with enhanced hippocampal memory formation (16). Memory formation and neuronal adaptation also involve GAP-43 expressed in the hippocampus (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it is of interest that bisphenol A exerts a powerful impact on neural system [14][15][16]. It was shown using a dose that is below the USEPA reference safe daily limit of 50 µg/kg/day [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in addition to developmental exposure to bisphenol A, there have been reported about exposure of adult animals to the chemical [14][15][16]. The current study was designed to examine whether exposure of adult rats to bisphenol A would cause neurodegeneration, particularly of dopaminergic neurons, resulting in a model of Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%